Silvopastoral systems with native trees: the economic, productive and social potential in the cerrado mineiro - Ribeiro, Felipe Corrêa (Universidade Federal de Viçosa, 2025)
The Cerrado is the most biodiverse savanna in the world, with a high rate of endemism and the provision of essential ecosystem services. Currently, the Cerrado presents a wide range of land uses and is constantly affected by land-use conversion due to its high agricultural productive potential. Among these uses, silvopastoral systems (SPS) with native trees stand out as an alternative model that integrates local biodiversity with economic practices of natural resource use. This research aims to clarify the current status of these systems and assess their economic, productive, and social potential in the Cerrado of northern Minas Gerais. In Chapter 1, we assessed the economic performance and sensitivity of the three main land uses in the region: agriculture, silvopastoral systems with native trees, and Eucalyptus plantations, with different sample sizes. For each system, we calculated gross margin and profitability indicators, considering income and both fixed and variable costs. Sensitivity analysis was conducted using a Monte Carlo simulation and a Random Forest model. The results revealed statistically significant differences in cost structure, income composition, and profitability across systems. Eucalyptus plantations showed the highest average profitability and the lowest economic risk, although they are highly dependent on external inputs (hired labor, market access, and infrastructure). SPS presented intermediate performance, with lower variable costs and potential ecological co-benefits, although their productive and commercial remains underutilized. Agriculture, primarily family-based and subsistence-oriented, showed the lowest profitability due to high fixed costs and limited market integration. Family labor was the main fixed cost component in both agriculture and SPS, strongly influencing the economic results. Despite the differences, low-risk farms were identified across all land uses, suggesting that profitability is achievable under supportive conditions. These findings underscore the importance of specific public policies that promote financial planning, technical assistance, and diversification of income sources in each land use. In Chapter 2, we investigated which productive, environmental, socioeconomic, technical, and farm-related factors influence the adoption and intensification of SPS with native trees. Based on interviews conducted with over 100 farmers, we used the Seemingly Unrelated Regressions (SUR) model, estimated through the Full Information Maximum Likelihood (FIML) method. Three equations were developed to assess the adoption of SPS, the intensification of its use through the generation of products, and the commercialization of these products. We found that 12 variables, distributed across the five groups of factors, influence the adoption and intensification of SPS differently. Water availability for production and the presence of family labor are key factors for intensification, although they do not directly affect adoption. In contrast, the age of farmers and their environmental awareness impact adoption but not intensification, often associated with older and more environmentally conscious farmers. Variables such as the total number of land uses and currently productive land uses positively affect all equations, while the distance between the farmer’s residence and the productive area has a negative effect. Based on these findings, we propose public policies targeting two groups, adopters and non-adopters, so that efforts to promote SPS with native trees focus not only on increasing adoption but also on intensifying its use. In Chapter 3, we investigated the NTFP market through interviews with traders located in the study region and major urban centers of the Cerrado in Minas Gerais. Using K-means clustering, we identified three market segments: small-scaled, medium-scaled, and large-scaled. The small-scaled market is characterized by low product diversity, predominantly unprocessed goods, and is found in municipalities with smaller populations, resulting in a more limited market. The medium-scaled market has the highest proportion of processed products and is present in the main municipalities of the study region but still has limited product diversity and volume. The large-scaled market includes traders located in large urban centers and the most populous municipality of the region, with higher commercialization levels, diverse suppliers, and a broad variety of products and species. Despite these differences, certain products such as pequi (Caryocar brasiliense) are found across all market segments, highlighting their commercial relevance. At the same time, each segment includes exclusive products, indicating a specialization in supply. The NTFP market context reveals a high economic and productive potential, particularly relevant for farmers who adopt SPS with native trees, given the variety of market scales and products identified. Keywords: land use; rural sustainability; non-timber forest products; economic analysis; farmers’ decision-making ; family farming; value chains; agroforestry systems; climate adaptation; productive diversification

O Cerrado é a savana com maior biodiversidade no mundo, com alta taxa de endemismo e a provisão de serviços ecossistêmicos essenciais. Atualmente, o Cerrado apresenta uma ampla gama de usos da terra e é constantemente afetado pela conversão do uso da terra devido ao seu alto potencial produtivo agrícola. Entre esses usos, os sistemas silvipastoris (SSP) com árvores nativas se destacam como um modelo alternativo que integra a biodiversidade local com as práticas econômicas de uso de recursos naturais. Esta pesquisa visa esclarecer o status atual desses sistemas e avaliar seu potencial econômico, produtivo e social no Cerrado do norte de Minas Gerais. No Capítulo 1, avaliamos o desempenho econômico e a sensibilidade dos três principais usos da terra na região: agricultura, sistemas silvipastoris com árvores nativas e plantações de Eucalipto, com diferentes tamanhos de amostra. Para cada amostra, calculamos a margem bruta e os indicadores de lucratividade, considerando a receita e os custos fixos e variáveis. A análise de sensibilidade foi conduzida usando uma simulação de Monte Carlo e um modelo de Random Forest. Os resultados revelaram diferenças estatisticamente significativas na estrutura de custos, composição da receita e lucratividade entre os sistemas. As plantações de Eucalipto mostraram a maior lucratividade média e o menor risco econômico, embora sejam altamente dependentes de insumos externos (mão de obra contratada, acesso ao mercado e infraestrutura). Os SSPs apresentaram desempenho intermediário, com menores custos variáveis e potenciais co-benefícios ecológicos, embora sua produtividade e comercialização permaneçam subutilizadas. A agricultura, principalmente familiar e de subsistência, mostrou a menor lucratividade devido aos altos custos fixos e à limitada integração ao mercado. A mão de obra familiar foi o principal componente de custo fixo tanto na agricultura quanto nos SSPs, influenciando fortemente os resultados econômicos. Apesar das diferenças, foram identificadas fazendas de baixo risco em todos os usos da terra, sugerindo que a lucratividade é alcançável sob condições favoráveis. Esses achados ressaltam a importância de políticas públicas específicas que promovam o planejamento financeiro, assistência técnica e diversificação das fontes de renda em cada uso da terra. No Capítulo 2, investigamos quais fatores produtivos, ambientais, socioeconômicos, técnicos e relacionados à fazenda influenciam a adoção e intensificação de SSPs com árvores nativas. Com base em entrevistas conduzidas com mais de 100 produtores rurais, usamos o modelo de Regressões Aparentemente Não Relacionadas (SUR), estimado através do método de Máxima Verossimilhança de Informação Completa (FIML). Três equações foram desenvolvidas para avaliar a adoção de SSPs, a intensificação de seu uso através da geração de produtos e a comercialização desses produtos. Descobrimos que 12 variáveis, distribuídas entre os cinco grupos de fatores, influenciam a adoção e a intensificação dos SSPs de forma diferente. A disponibilidade de água para produção e a presença de mão de obra familiar são fatores-chave para a intensificação, embora não afetem diretamente a adoção. Em contraste, a idade dos produtores e sua consciência ambiental impactam a adoção, mas não a intensificação, sendo frequentemente associados a produtores mais velhos e com maior consciência ambiental. Variáveis como o número total de usos da terra e os usos da terra atualmente produtivos afetam positivamente todas as equações, enquanto a distância entre a residência do produtor e a área produtiva tem um efeito negativo. Com base nesses achados, propomos políticas públicas que visem a dois grupos, adotantes e não adotantes, para que os esforços para promover os SSPs com árvores nativas se concentrem não apenas em aumentar a adoção, mas também em intensificar seu uso. No Capítulo 3, investigamos o mercado de PFNM através de entrevistas com comerciantes localizados na região de estudo e nos principais centros urbanos do Cerrado em Minas Gerais. Usando a clusterização K-means, identificamos três segmentos de mercado: pequena escala, média escala e grande escala. O mercado de pequena escala é caracterizado pela baixa diversidade de produtos, predominância de produtos não processados e é encontrado em municípios com populações menores, resultando em um mercado mais limitado. O mercado de média escala tem a maior proporção de produtos processados e está presente nos principais municípios da região de estudo, mas ainda possui diversidade e volume de produtos limitados. O mercado de grande escala inclui comerciantes localizados em grandes centros urbanos e no município mais populoso da região, com maiores níveis de comercialização, fornecedores diversificados e uma ampla variedade de produtos e espécies. Apesar dessas diferenças, certos produtos como o pequi (Caryocar brasiliense) são encontrados em todos os segmentos de mercado, destacando sua relevância comercial. Ao mesmo tempo, cada segmento inclui produtos exclusivos, indicando uma especialização no fornecimento. O contexto do mercado de PFNM revela um alto potencial econômico e produtivo, particularmente relevante para os agricultores que adotam SPS com árvores nativas, dada a variedade de escalas de mercado e produtos identificados. Palavras-chave: uso da terra; sustentabilidade rural; produtos florestais não madeireiros; análise econômica; tomada de decisão agrícola; agricultura familiar; cadeias de valor; sistemas agroflorestais; adaptação climática; diversificação produtiva.
Sistemas silvipastoris com árvores nativas: O potencial econômico, produtivo e social no cerrado mineiro
Keywords: Cerrados - Minas Gerais; Agrossilvicultura; Solo - Uso; Sustentabilidade; Produtos florestais; Agricultura familiar; Monte Carlo, Método de; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL